IPD-MHC: nomenclature requirements for the non-human major histocompatibility complex in the next-generation sequencing era - Maccari, Giuseppe (Immunogenetics, 2018)
The IPD-MHC Database is the official repository for non-human MHC sequences, overseen and supported by the Comparative MHC Nomenclature Committee, providing access to curated MHC data and associated analysis tools. To address the increasing amount and complexity of data being submitted, an entirely upgraded version of the IPD-MHC Database was recently released to maintain IPD-MHC as the central platform for the comparison of curated MHC data. As a consequence, a new level of nomenclature standardisation is required between the different species to enable data submission and to allow the unambiguous inter- and intra-species comparison of alleles. However, any changes must retain the flexibility demanded by the unique biology of different taxonomic groups. Here, we describe the rationale for a standardised nomenclature system and summarise the changes that have been driven by the requirements of implementing the IPD-MHC database. This modified nomenclature system is essential to maintain the current functionality of IPD-MHC and provide a scalable future-proof database organisation to fully exploit the bioinformatic tools used for analysis.